Comparative Study on the Tensile Properties of Thermoplastic Corn Starch Films Reinforced with Cornhusk and Stalk Fillers - Ahmed Edhirej; Mohamed Fargani; Mohammed Hepa (Journal of Scientific and Human Dimensions, 2026)
With rising concerns regarding non-biodegradable waste in today's environment, there has been growing interest in naturally available fiber-reinforced bio composites, especially those derived from agro-waste resources. In this regard, this study presents a comparative evaluation of the tensile properties of thermoplastic corn starch (TPS) films reinforced with two types of filler materials obtained from corn: Corn Husk (CHF) and Corn Stalk (CSF). Bio composite films were developed by solution-casting using fructose as a plasticizer, with 2% to 8% fiber content. Results indicate distinct reinforcing behaviors between these two types of filler materials. In contrast to composites reinforced with CHF, a higher tensile modulus of the films reinforced with CSF can be due to the rigid nature of the stalk fibers. At the same time, however, higher brittleness and lower elongation at break of the CSF-reinforced films suggest that despite rigidity, there is a reduction in flexibility. CHF-reinforced films tended to have better tensile strength and higher elongation at break values, which would demonstrate higher flexibility than CSF-reinforced films. Based on 8% CHF content, films achieved an optimal balance between tensile strength and flexibility. Thus, from an efficiency standpoint, it can be concluded that Corn Husk is more suitable than Corn Stalk for creating flexible and environmentally friendly food packaging materials.
Keywords: Tensile Properties; Bio composites; Thermoplastic Starch; Interfacial Adhesion; Corn Husk/Stalk; Fracture Behavior